Effects of VEGF-A165b and SRPK1 inhibition on pain behaviour, cyclooxygenase expression and glial activation in the CNS in a model of osteoarthritis - Almahasneh, Fatimah (2018)
Background: Osteoarthritis (OA) is the most common musculoskeletal disease worldwide and a major cause of chronic pain. Treatment of OA pain is still suboptimal due to limited efficacy and considerable side effects of available analgesics. Pain in OA has a significant central component. Cyclooxygenases (COXs) and glial cells in the spinal cord and the periaqueductal gray (PAG) play a significant role in central sensitisation and pain modulation. Vascular endothelial growth factor-A (VEGF-A) is a key molecule in normal and pathological angiogenesis. Serine arginine protein kinase 1 (SRPK1), which phosphorylates serine arginine splice factor 1 (SRSP1), controls VEGF gene alternative splicing. This results in two splice variants; VEGF-A165a, which is pro-angiogenic and pro-nociceptive, and anti-angiogenic VEGF-A165b, which showed anti-nociceptive effects in models of neuropathic and inflammatory pain. Objective: This thesis investigated changes in COX expression and glial activation in the spinal cord and the PAG in the monosodium iodoacetate (MIA) model of OA. It also addressed the effects of VEGF-A165b and SRPK1 inhibitor SPHINX-31 on pain behaviour and joint pathology, as well as COX expression and glial activation in the spinal cord and the PAG in the same model. Hypothesis: VEGF-A165b and SPHINX-31 can prevent and/or reverse enhanced pain behaviour in the MIA model of OA, through involvement of spinal glial cells and COXs in the PAG and spinal cord. Vascular-astrocyte association in the PAG is enhanced in the MIA model of OA, and this effect is reversed by administration of SPHINX-31. Methods: Rats received an intra-articular injection of MIA (1 mg) in the knee. In one study, animals were treated with VEGF-A165b (i.p. 20 ng/g body weight twice weekly) on days 0-13 (VEGF(d0-13) group) or days 14-28 (VEGF(d14-28) group) after MIA injection; in another study, rats received SPHINX-31 (i.p. 0.8 µg/g body weight twice weekly; (MIA/SPHINX group)) for 19 days after induction of the model. Pain behaviour was monitored throughout the studies, at the end of which (day 28) tissues were collected for the assessment of joint histopathology and the evaluation of spinal COX-2 mRNA expression by PCR. In addition, immunofluorescence (IF) was used to assess COX-2 expression and glial activation in the spinal cord, as well as astrocyte activation and vascular-astrocyte association in the PAG. Results: VEGF-A165b significantly attenuated weight bearing asymmetry (%) in MIA rats on day 28 (29.58 ± 1.803 in MIA/VEGF(d0-13) group vs. 22.95 ± 2.088 in MIA/PBS group, p<0.01; 29.23 ± 1.49 in VEGF(d14-28) vs. 22.95 ± 2.088 in MIA/PBS, p<0.05). VEGF-A165b reversed mechanical withdrawal thresholds to the naïve level, but without reaching statistical significance. No significant changes in knee joint pathology were observed in VEGF-A165b treated MIA rats compared to the MIA/PBS counterparts. In the MIA/VEGF(d0-13) group, contralateral deep laminae of the dorsal horn had a higher percentage (%) of non-neuronal cells expressing COX-2 than the corresponding superficial laminae (3.26 ±1.16 vs 1.12 ± 0.43, p<0.05), while no difference was observed in the MIA/PBS group. Administration of VEGF-A165b did not significantly affect spinal microglia and astrocyte activation, nor COX-2 expression in the PAG. SPHINX-31 had no significant effects on pain behaviour, joint pathology or spinal COX-2 expression in the MIA model of OA. On the other hand, MIA/SPHINX group exhibited a higher activation of spinal microglia than MIA controls (% of CD11b +ve cells in MIA/SPHINX-31 vs MIA/vehicle groups: 6.36 ± 0.89 vs 1.72 ± 0.38, p<0.01). In addition, SPHINX-31 significantly increased astrocyte activation in the ipsilateral dorsolateral (DL) PAG relative to corresponding ventrolateral (VL) PAG (GFAP IF intensity: 12.89 ± 1.52 vs 8.46 ± 0.84, p<0.05), and it increased vascular-astrocyte association (%) in the contralateral DL PAG relative to corresponding VL PAG (70.35 ± 7.68 vs 38.92 ± 8.19, p<0.05). Interestingly, naïve rats had a significantly higher astrocyte activation and vascular-astrocyte association in the VL PAG than in DL PAG. Conclusions: VEGF-A165b exerted a significant antinociceptive effect in the MIA model of OA without affecting joint pathology, spinal glial cell activation or COX-2 expression in the PAG. SPHINX-31 did not reverse pain behaviour, but showed a potential effect on astrocyte activation and vascular-astrocyte association in the DL PAG relative VL PAG in the MIA model of OA.